Mexico, Social Accounting Matrix (SAM), 1996 - International Food Policy Research Institute (International Food Policy Research Institute, 2002)
This is a regionalized SAM of Mexico, which differentiates production across five regions, four rural and a fifth "national" urban region. The rural regions are differentiated by their agricultural production technologies. There are three households in each region, disaggregated by income level, for a total of 15 households. Each rural region has 6 agricultural production activities, which are destined to national commodity markets, plus one national livestock-forestry-fisheries sector. The urban region contains 14 other production sectors. Each rural region has its own agricultural labor and its own irrigated and non-irrigated land. The urban region employs 4 labor types: professional, white collar, blue collar and unskilled/informal. One capital factor is used by all regions. For a description of the construction and use of this dataset, download the Trade and Macroeconomics Division Discussion Paper Number 97: (PDF 260K)